Mother's Education and Employment Status: Non-Factors in Children's School Readiness: Pendidikan dan Status Pekerjaan Ibu: Bukan Faktor dalam Kesiapan Anak untuk Sekolah Dasar - Lely Ika Mariyati; Dwi Nastiti; Dyah Rizqi Nurdiani Fitri; Azizah Alifia Salsabila; Kevin Meicello Dwita (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to analyze the influence of mother's education level and employment status on children's readiness for elementary school. Employing a quantitative comparison method, data from 194 children were collected through the NST test and a parental questionnaire. The school readiness, mother's education level, and employment status were assessed. Statistical analysis using SPSS 16.0 and the Anova and t-test techniques revealed that neither the mother's education level (F = 1.139, Sig. = 0.340 > 0.05) nor the employment status (t score = -0.763, Sig. = 0.446 > 0.05) significantly influenced the school readiness of the children. These results suggest that other intervening variables such as parenting styles, socioeconomic status, and child's motivation may be more crucial determinants of a child's preparedness for school. This study offers a novel perspective to parents, educators, and developmental psychologists by challenging conventional assumptions about mother's influence on children's school readiness. Highlights: A mother's education level doesn't significantly influence a child's readiness for elementary school. A mother's employment status (working or non-working) also doesn't significantly affect a child's school readiness. Other factors like parenting styles, socioeconomic status, and child's motivation could be more influential on a child's preparedness for school. Keywords : School Readiness, Mother's Education Level, Working Mother, Not Working Mother